Toxicity of zinc oxide nanoparticles on the embryo of Javanese medaka Oryzias javanicus Bleeker, 1854: a comparative study - Amin, Naweedullah; Zulkifli, Syaizwan Zahmir; Azmai, Mohammad Noor Amal; Ismail, Ahmad (Multidisciplinary Digital Publishing Institute, 2021)
(1) Background: Zinc oxide nanoparticles (ZnO NPs) are widely applied in various human products. However, they can be extremely toxic for aquatic organisms, particularly fish. This research was conducted to determine the LC50 of ZnO NPs on the embryos of Javanese medaka (Oryzias javanicus) in ultra-pure, deionized, and dechlorinated tap water; (2) Methods: The experiments were conducted in a completely randomized design (CRD) with three replicates for six treatments for acute (0.100, 0.250, 0.500, 1.00, 5.00, and 10.00 mg/L) exposures for each type of water; (3) Results: The LC50 of ZnO NPs at 96 h was determined as 0.643 mg/L in ultra-pure water, 1.333 mg/L in deionized water, and 2.370 in dechlorinated tap water. In addition to concentration-dependent toxicity, we also observed time-dependent toxicity for ZnO NPs. In addition, the sizes of ZnO NPs increased immediately after dispersion and were 1079 nm, 3209 nm, and 3652 nm in ultra-pure, deionized, and dechlorinated tap water. The highest concentration of measured Zn2+ in exposure concentrations was found in ultra-pure water, followed by deionized and dechlorinated tap water suspensions. Furthermore, Javanese medaka showed high sensitivity to acute exposure of ZnO NPs in all types of water.